Precessional Cyclicity of Seawater Pb Isotopes in the Late Miocene Mediterranean. Issue 12 (29th December 2019) - Modestou, S. E.; Gutjahr, M.; van der Schee, M.; Ellam, R. M.; Flecker, R.
Abstract: Astronomical tuning in the Mediterranean region is primarily based on organically‐mediated proxies, such as cyclicity of organic rich layers or changes in foraminiferal assemblages. Both during and post deposition, organic proxies can be affected by complex processes not immediately related to the changes in precession (insolation) they are assumed to reflect. Here we present an isotopic proxy which exhibits precessional cyclicity yet is inorganic. Seawater lead (Pb) isotope records over four precessional cycles between 6.6 and 6.5 Ma, from bulk sediment leachates of three Messinian, circum‐Mediterranean marginal locations, show variations consistent with precessional cyclicity. During insolation minima, the Pb isotope signatures from all three sites converge to similar values, suggesting a regional process is affecting all three locations at that time. Data from the marginal sites are compared with new data from ODP Site 978 and published data from a variety of geological archives from the Mediterranean region to determine the mechanism(s) causing the observed variability. While the comparisons are not fully conclusive, the timing of events suggest that increased dust production from North Africa during insolation minima is the most likely control. This hypothesis implies that authigenic marine Pb isotope records have the potential to provide a reliable inorganic tie point for Mediterranean cyclostratigraphy where sub‐precessional resolution is required. An inorganic tie point could also provide the means to resolve long‐standing problems in Mediterranean stratigraphy on precessional and sub‐precessional timescales which have been obscured due to post‐depositional changes (e.g., sapropel burn‐down) or suboptimal ecological conditions (e.g., the Messinian Salinity Crisis). Plain Language Summary: Research into the geological and climate history of the Mediterranean region has been important globally, partly because the geologic timescale, back to about 23 million years ago, is pinned to the geological record of this region and partly because the water exiting the Mediterranean into the Atlantic is an important component of global ocean circulation. In this paper, we examine changes through time in the isotope ratios of the trace metal lead (Pb), which is present in tiny amounts even in unpolluted seawater. Our Pb isotope records, covering ~100 thousand years at about 6.5 million years ago, show distinctive regular cyclicity with time, with "peaks" at approximately 20 thousand year intervals. We hypothesize that wet‐dry climate cycles in North Africa produced these peaks by supplying more dust to the Mediterranean during the driest part of the cycle, when Pb from dust would have more strongly influenced the seawater Pb isotope composition. This hypothesis is exciting because it suggests that seawater Pb isotopes have the potential to improve our understanding of the passage of time in the Mediterranean region, in particular at times and locations where existing techniques are inadequate. Key Points: Precessional cyclicity is exhibited in records of seawater Pb isotopes from marginal Messinian Mediterranean marine sediments We hypothesize that dust from North Africa drives the observed cyclicity Seawater Pb isotopes in the Mediterranean potentially provide another tie point to anchor the insolation curve for orbital tuning